ANALYSIS OF THE MAIN GENERATOR DUAL FUEL DIESEL ELECTRIC (DFDE) 12V50DF SUDDEN TRIP - Yando, Markus; Amiruddin, Amiruddin; Wahyudi, Bambang; Pengestu N, Ryan (Dinasti International Journal of Digital Business Management, 2021)
In the 20th century, the growth of marine transportation has grown rapidly in line with technological advances. Given that the marine transportation sector is one of the pollutants that exist today, the use of energy sources with better thermal efficiency and combustion that does not have a negative impact on the environment is needed in the modern era. In accordance with the regulations stipulated by IMO in the Marine Polution (Marpol) Annex VI Regulation 14 which regulates the prohibition of ships from using fuels with sulfur content higher than 0.5%. The need for alternative fuels in the shipping industry is an important thought to support the efficiency of the shipping industry. Liquid Natural Gas (LNG) is currently being developed by the government as a fuel for vehicles and environmentally friendly industries. In addition to its availability, natural gas is also considered effective for combustion. Methane / LNG gas is one of the most dominant alternative fuels at this time. This fuel can also save company expenses, namely reducing the cost of providing fuel for energy needs as a source of propulsion on board the ship. For the above, ships, especially LNG carriers, have used a lot of diesel engines to propel their ships using LNG fuel with the concept of the engine being Two Fuel Diesel Electric (DFDE) where the engine can use Marine Diesel Oil (MDO) and LNG. The DFDE engine drives the Generator and the Generator generates electricity to drive the Electric Motor and the Electric motor moves the propeller shaft, this DFDE engine in the future will replace conventional diesel engines because it is more cost efficient, but requires Engineers who understand DFDE engine technology.